PERAN LOKASI DAN STRATEGI PENJUALAN DALAM MENSTABILKAN PENDAPATAN UMKM: STUDI KASUS RUMAH MAKAN PADANG - Angelicia, Natasya; Rahmawati, Indah; Hendri, Ade Karsari Zulmi; Kahaikal, Randy; Prasetyo, Johan Hendri (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
Padang restaurants are one of the micro, small, and medium enterprises (MSMEs) offering a variety of typical Minangkabau cuisine from Padang, West Sumatra. In the capital city of Jakarta, there are many Padang restaurant MSMEs with tight competition and various sales methods. Each Padang restaurant has different incomes, depending on its sales strategy and competitiveness in the market. To compete and maintain its income, business owners must have an effective sales strategy. This study aims to understand how the location of the business, sales strategies, and income variations affect the performance of Padang restaurant businesses. The subject of this research is the Padang Restaurant Ampera Saiyo Tipar Cakung. Data collection methods were carried out through field research, direct observation, interviews with owners and employees, and collection of related business documents. The collected data were analyzed using a qualitative case study approach. The observation results show that at the location of Padang Restaurant Ampera Saiyo, there are also two other competitors. When one competitor is not operating, customers tend to switch to Ampera Saiyo restaurant, and vice versa. The problem often faced by Padang Restaurant Ampera Saiyo is income instability. The factors influencing this instability are competition among Padang restaurants. To overcome this challenge, one of the sales strategies applied is to utilize digital marketing, such as GoFood and GrabFood, to expand market reach and increase visibility of Padang Restaurant Ampera Saiyo among potential customers.